2015
DOI: 10.1080/11745398.2015.1037324
|View full text |Cite
|
Sign up to set email alerts
|

At home away from home: visitor accommodation and place attachment

Abstract: Second-home owners often establish deep connections with their dwellings, and the broader landscapes of which these dwellings are part. In this research, we consider whether, and to what extent, visitors to commercial tourist accommodation also experience feelings of place attachment and home. These issues were investigated via a case study approach, centred on a youth hostel located in a high-amenity coastal area of New Zealand. The hostel's publicly available visitor books were analysed to draw out expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The extensive scholarship on second-home tourism points to a tendency to mix touristic needs and activities with everyday life environments (Marjavaara, 2008;Mottiar & Quinn, 2003;M€ uller, 2011). The second-home tourism contexts highlights how tourist experiences are possible physically very close to home, while at the same time demonstrating the importance of building place attachment and a sense of familiarity through tourism, at places other than one's main residence (Wildish, Kearns, & Collins, 2016). In sum, subjectivities of proximity and distance are central to one of the main paradoxes of tourism.…”
Section: Pull Factormentioning
confidence: 99%
“…The extensive scholarship on second-home tourism points to a tendency to mix touristic needs and activities with everyday life environments (Marjavaara, 2008;Mottiar & Quinn, 2003;M€ uller, 2011). The second-home tourism contexts highlights how tourist experiences are possible physically very close to home, while at the same time demonstrating the importance of building place attachment and a sense of familiarity through tourism, at places other than one's main residence (Wildish, Kearns, & Collins, 2016). In sum, subjectivities of proximity and distance are central to one of the main paradoxes of tourism.…”
Section: Pull Factormentioning
confidence: 99%
“…However, this relationship had no clear conclusion so far in prior studies. Some studies argued that perceived authenticity could be impacted by place attachment [14,15], while other studies suggested the opposite relations [4,[18][19][20]. Few studies have focused on how to utilize the authentic experience to make tourists more attached to a destination.…”
Section: Introductionmentioning
confidence: 99%
“…This also stems from the common view on relatively weak affective bonds with place among mobile individuals (Cuba and Hummon, 1993), confronted with the general reluctance towards further re-location among those expressing strong place attachment (Tuulentie and Heimtun, 2014). Since "modernity has changed society to a state of great mobility where people have social networks beyond their local area" (Aronsson, 2004, p. 75), however, the notion of a second home presupposes sharing place attachment in two or more (multiple) distinct locations: permanent and holiday home(s) (Wildish et al, 2016).…”
Section: Place Attachmentmentioning
confidence: 99%